Nursing services as perceived by inmates in correctional facilities in Jakarta, Indonesia: A qualitative study - Wilma Wilma; Achir Yani S. Hamid; Hanny Handiyani; Ede Surya Darmawan (Belitung Nursing Journal, 2023)
Background: Nursing services play a crucial role in addressing the healthcare needs of inmates in correctional facilities while upholding their human rights. However, delivering nursing services in this context is challenging. Unfortunately, there is a dearth of research on this topic in Indonesia. Objective: This study aimed to explore the experiences of inmates in receiving nursing services in order to provide insights into professional nursing services in the correctional context in Indonesia. Methods: A qualitative phenomenological approach was used in this study. Twenty inmates were selected purposively from four prisons, three jails, and one child penitentiary in Jakarta, Indonesia. Semi-structured in-depth interviews were conducted from August to October 2021, and thematic analysis was used to analyze the data. Results: Five themes were generated: (1) conditions requiring nursing services, (2) types of nursing services received, (3) nurse competence, (4) barriers to receiving nursing services, and (5) expectations for nursing services in the future. Conclusion: This study highlights the importance of nursing services in correctional facilities and the unique challenges that correctional nurses face in providing services professionally and ethically. Strategies to enhance nursing services, advance nurse competence, and reduce barriers to accessing care are needed to improve inmates’ health outcomes.